Tubercular Lymphadenitis - A Quiet and Persistent Form of Tuberculosis - Vaishnavi Shankar; Vasantha Kamath (APIK Journal of Internal Medicine, 2026)
Abstract Tubercular lymphadenitis is the most common form of extrapulmonary tuberculosis (TB) and accounts for up to 43% of peripheral lymphadenopathy in the resource-limited settings. It predominantly affects young adult women and presents as painless, slowly enlarging cervical lymph nodes that may progress through discrete, matted, caseating, collar-stud, and sinus stages if left untreated. Globally, the epidemiology of lymph node mycobacterial disease is geographically polarized. In high-burden countries such as India, which accounts for 26% of the global TB burden, Mycobacterium tuberculosis remains the dominant pathogen. In high-income countries, the cessation of Bacillus Calmette–Guérin (BCG) vaccination has led to a resurgence of nontuberculous mycobacterium (NTM) lymphadenitis, underscoring BCG’s protective role beyond pulmonary TB. The diagnosis requires a composite approach that combines fine-needle aspiration cytology, Xpert MTB/RIF (CBNAAT), culture, and imaging. No single test is diagnostic. Treatment follows standard anti-TB therapy (2HRZE/4HR) for drug-susceptible disease, with extension to 9–12 months in complex cases. Paradoxical reactions occur in 20%–30% of patients and should not prompt a change in treatment. India has made significant programmatic progress, reducing TB incidence from 322 per 100,000 in 2000 to 195 per 100,000 in 2023 and mortality from 87 to 22 per 100,000 over the same period. Despite this, lymph node TB remains a substantial contributor to the extrapulmonary disease burden. Clear, standardized guidelines specific to lymph node TB are essential to sustain and accelerate this progress.